Improving Writing Skill of the Tenth-Grade Students through Think-Pair-Share Combined with Picture - Putri, Ermelinda Aldianingsi; Sawitri, Ni Luh Putu Dian; Maharani, Anak Agung Putri (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2025)
The present classroom action research was mainly based on the preliminary study conducted on the subjects of the study, the tenth-grade students of SMK Rekayasa Denpasar in the academic year 2024/2025. The objective of the study was intended to find out whether writing skill of the tenth-grade students of SMK Rekayasa Denpasar in the academic year could be improving through think-pair-share combined with picture. Thus, to achieve the objective, the researcher conducted classroom action research in two cycles. The research instrument such as, tests and questionnaire, were administered to collect the required data. The data were then analyzed by comparing the results of the pre-test and post-test, which showed there were significant improvements in the subjects mean scores from the pre-test to post-test. As the supporting data, the questionnaire was also administered at the end of the last cycle, and the results showed positive responses on the implementation of think-pair-share combined with picture. It was found that writing skill of the tenth-grade students of SMK Rekayasa Denpasar in the academic year 2024/2025 can be improved through think-pair-share combined with picture.